DIGITAL BILLBOARDS AND BEYOND: HOW THE 4TH INDUSTRIAL REVOLUTION IS RESHAPING OUTDOOR ADVERTISING - Steyn, Charles Edmund; Groenewald, Helen Patricia (Ayden Journal of Management and Social Sciences, 2024)
Advertising, driven by the innate human senses, serves the fundamental purposes of informing, persuading, and reminding. Among its various forms, outdoor advertising, or Out-of-Home (OOH) advertising, stands as one of the oldest, with origins tracing back to ancient Egyptian hieroglyphics. The evolution of advertising witnessed significant milestones, including Johannes Gutenberg's invention of movable type printing in the 1400s, which paved the way for modern advertising formats like leaflets. Subsequently, the introduction of lithography in 1796 revolutionized printing methods, enabling the emergence of posters and marking a pivotal moment in OOH advertising history. This review explores the historical trajectory of outdoor advertising, highlighting its evolution from ancient origins to modern-day practices, and underscores its enduring significance in the advertising landscape.